Healthy Young POLes – HYPOL database with synchronised beat-to-beat heart rate and blood pressure signals: HYPOL – Cardiovascular Time Series Database - Guzik, Przemysław; Krauze, Tomasz; Wykrętowicz, Andrzej; Piskorski, Jarosław (Journal of Medical Science, 2023)
Data sharing in medical research entails making research data available to other researchers for review, reuse, and collaboration. This paper seeks to describe the HYPOL (Healthy Young POLes) database, which has been prepared for sharing. This database houses the clinical characteristics and beat-to-beat cardiovascular time series of 278 individuals of Polish descent, all aged between 19 and 30 years. The data were collected from healthy volunteers who participated in multiple projects at the Department of Cardiology-Intensive Therapy research laboratory, Poznan University of Medical Sciences, Poznan, Poland. The cardiovascular time series data was obtained from non-invasive continuous finger blood pressure and ECG recordings, with sessions lasting up to 45 minutes. The HYPOL database includes an xls file detailing the main clinical characteristics and text files that capture ECG-derived RR intervals, finger systolic, diastolic, and mean blood pressure values, as well as the duration of interbeat intervals.The data is from 149 women (53.6% of the total) and 129 men. The median age of all participants studied was 24 years, their BMI was